An inconsistency between light speed invariance and causal relations - Rossey, Luk (Physics essays, 2018)
If the speed of light is independent of the movement of its source, then it should make no difference at all when clocks are synchronized using light sources at rest or moving ones. It seems it does. When clocks are synchronized in two reference frames, moving relatively to one another, the causal relations between two particular events will depend on whether sources at rest or moving ones have been used. This inconsistency will appear solid evidence that the speed of light can never be invariant.